PENGARUH KESADARAN MEREK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA CV KAOS POLOS MANIA (KPM APPAREL) CABANG KOTA DEPOK - Yusfa Muhammad Bakran; Ela Hulasoh (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of brand awareness and brand image on purchasing decisions. The method used is a causal quantitative associative approach. Data collection was carried out through direct observation in-store, distribution of questionnaires to consumers, and documentation of observation results such as sales and pricing data. The sampling technique uses accidental sampling with the Slovin formula; from a population of 1,019 respondents, a sample of 91 respondents was obtained. Data analysis includes validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing using SPSS version 26. The research results show that brand awareness has a significant influence on purchasing decisions, with a determination coefficient value of 50.2%. The hypothesis test shows that the t-value (9.446) is greater than the t-table (1.988). Brand image also has a significant influence on purchasing decisions, with a determination coefficient of 79.4% and a t-value (10.877) greater than the t-table (1.988). Simultaneously, brand awareness and brand image have a significant influence on purchasing decisions, with a regression equation of Y=3.862+0.234X1+0.497X2Y = 3.862 + 0.234X_1 + 0.497X_2Y=3.862+0.234X1+0.497X2. The total determination coefficient reaches 61%, while the remaining 39% is influenced by other factors. The hypothesis test shows that the calculated F-value (68.961) is greater than the F-table (3.10), with a significance level of 0.000 < 0.050, indicating a significant influence of Brand Awareness and Brand Image on Purchasing Decisions CV.l Kalos Polos Malnial (KPM Apparel) Depok City Branch.